De' Shona Enterprise - Linus, Melissa; Calingacion, Wendy Joy; Saiman, Nur Afiqah; Umar Sarim, Nisha Karmila; Abu Bakar, Syahirah Adriana (2015)
De' Shona Enterprise was founded in 2013 and is manufacture a Spray-on Sunscreen machines. Our principal offices are located in , Exit Jalan Tun Fuad Stephen, 88000 Kota Kinabalu, Sabah. The management team is led by the Chief Executive Manager, Wendy Joy Calingacion who founded the company in 2013 and incorporated the company after having enough partners of 4 which hold different positions. The partners are Syahirah Adriana binti Abu Bakar, Nisha Karmila binti Umar Sarim, Nur Afiqah binti Saiman and Melissa Linus. De' Shona enterprise makes a convenient and effective skin care solution in the fight against the world wide epidemic of skin care. We are using Nivea Sun product in our Spray-on Sunscreen machine. We define our market as a world skin cancer free since we providing a skin care solution to our customers regarding their ages and genders. Some of our most notable customers include those who participate outdoor activities actively.